Processing of audiovisual associations in the human brain: dependency on expectations and rule complexity - Lindström, Riikka; Paavilainen, Petri; Kujala, Teija; Tervaniemi, Mari (Frontiers in Psychology, 2012)
In order to respond to environmental changes appropriately, the human brain must not only be able to detect environmental changes but also to form expectations of forthcoming events. The events in the external environment often have a number of multisensory features such as pitch and form. For integrated percepts of objects and events, crossmodal processing and crossmodally induced expectations of forthcoming events are needed. The aim of the present study was to determine whether the expectations created by visual stimuli can modulate the deviance detection in the auditory modality, as reflected by auditory event-related potentials (ERPs). Additionally, it was studied whether the complexity of the rules linking auditory and visual stimuli together affects this process. The N2 deflection of the ERP was observed in response to violations in the subjects' expectation of a forthcoming tone. Both temporal aspects and cognitive demands during the audiovisual deviance detection task modulated the brain processes involved.